Energy efficient and environmentally friendly technology of stabilizing airline enterprises’ wastewater sludges - Шаманський, Сергій Йосипович; Бойченко, Сергій Валерійович (Eastern-European Journal of Enterprise Technologies, 2015)
Various utilization methods of wastewater sludges were considered. It is shown that their use as organic fertilizer can be considered as the most promising. However, their preliminary stabilization is necessary to prevent further decay and to get rid of pathogens. Many traditional methods of anaerobic fermentation and conventional designs of the digests were analyzed. It is shown that all of them have a significant number of shortcomings, making them not always cost effective and environmentally friendly. A variety of intensification methods of anaerobic fermentation processes was examined. It is shown that the methods of separation of different fermentation stages, such as hydrolysis, acidogenesis, acetogenesis, and methanogenesis in space (when these stages proceed in different tanks) and in time (when done consistently) may be the most promising. Different strains of bacteria that are responsible for different fermentation stages grow in many cases far more rapidly when separated one from the other. Anaerobic processes occurring at different fermentation stages were investigated. The most important parameters and their optimal values for each stage were also identified. Based on this, a new fermentation technology, which allows to intensify the process, significantly reduce the fermentation duration, produce commodity carbon dioxide, environmentally clean organic fertilizer, as well as biogas with significantly higher methane content than with traditional technologies, was proposed.